Food-borne fungi and their secondary metabolites (mycotoxins): the Penicillium case - Lima, Nelson (2018)
Penicillium Link is the most ubiquitous and unavoidable fungi in nature. If a genus level it is quite straightforward to identify because of its “little brush” distinctiveness, the identification at species level is difficult. Penicillia species are complex from a biological perspective, which contributes to the identification problem. To perform a sound classification or identification a polyphasic identification is strong recommended. Mycotoxins are fungal secondary metabolites which cause sickness or death in people when ingested, inhaled, and/or absorbed and they can occur and co-occur naturally in different food commodities. Taking into consideration that the Penicillia, or their associated mycotoxins, continue deteriorate economical relevant food commodities is the aim of this work present the state-of-the-art on Penicillia identification and emergent species as potential mycotoxigenic food-borne fungi. The apples, hard cheese and red pepper (chilli) will be used as case studies and the mycotoxins patulin and ochratoxin A (OTA) the main focus of these food contaminations. To address these issues classic and molecular identification will be discussed and the analytical methods associated with molecular probes for respectively mycotoxins quantification and detection will be also discussed. The difficulties of correlate the mycobiota load presents in different food commodities with mycotoxins detected will be also presented and discussed. Finally, it will be concluded that to address correctly food risk assessment elucidations are urgent needed to associate the putative ochratoxigenic species and OTA biosynthetic metabolic pathway.